ANALISIS KINERJA PERUSAHAAN SEBELUM DAN SESUDAH BERPARTISIPASI DALAM CORPORATE GOVERNANCE PERCEPTION INDEX (CGPI) - TRILENI, MEI (Jurnal Akuntansi AKUNESA, 2014)
Good Corporate Governance is the key to successfully company to grow and flourish so as to produce a profit in the long run. The concep of corporate governance arises as an effort to control or overcome behavior management is selfish. This research aims to know the comparative performance of the companies participating in the Corporate Governance Perception Index as well as the regulation of Bapepam-LK No: Kep-134/BL/2006. A method of research using approach descriptive quantitative. The result showed the existance of the regulation of Bapepam-LK No: Kep-134/BL/2006, company performance PT. Aneka Tambang Tbk be increased.Keywords: Corporate Governance Perception Index (CGPI), Bapepam-LK No: Kep-134/BL/2006, return on equity